The Incidence of Postoperative Seizures Following Treatment of Postinfectious Hydrocephalus in Ugandan Infants: A Post Hoc Comparison of Endoscopic Treatment vs Shunt Placement in a Randomized Controlled Trial. Issue 4 (13th May 2019) - Punchak, Maria; Mbabazi Kabachelor, Edith; Ogwal, Michael; Nalule, Esther; Nalwoga, Joyce; Ssenyonga, Peter; Mugamba, John; Rattani, Abbas; Dewan, Michael C; Kulkarni, Abhaya V; Schiff, Steven J; Warf, Benjamin
Abstract: BACKGROUND: There are currently no published data directly comparing postoperative seizure incidence following endoscopic third ventriculostomy (ETV), with/without choroid plexus cauterization (CPC), to that for ventriculoperitoneal shunt (VPS) placement. OBJECTIVE: To compare postoperative epilepsy incidence for ETV/CPC and VPS in Ugandan infants treated for postinfectious hydrocephalus (PIH). METHODS: We performed an exploratory post hoc analysis of a randomized trial comparing VPS and ETV/CPC in 100 infants (<6 mo old) presenting with PIH. Minimum follow-up was 2 yr. Variables associated with and the incidence of postoperative epilepsy were compared (intention-to-treat) using a bivariate analysis. Time to first seizure was compared using the Kaplan–Meier method, and the relative risk for the 2 treatments was determined using Mantel-Haenszel hazard ratios. RESULTS: Seizure incidence was not related to age ( P = .075), weight ( P = .768), sex ( P = .151), head circumference ( P = .281), time from illness to hydrocephalus onset ( P = .973), or hydrocephalus onset to treatment ( P = .074). Irritability ( P = .027) and vision deficit ( P = .04) were preoperative symptoms associated with postoperative seizures. Ten (10%) patients died, and 20 (20%) developed seizures over the follow-up period. Overall seizure incidence was 9.4 per 100 person-years (9.4 and 9.5 for ETV/CPC and VPS, respectively; P = .483), with no significant difference in seizure risk between groups (hazard ratio, 1.02; 95% CI: 0.42, 2.45; P = .966). Mean time to seizure onset was 8.5 mo for ETV/CPC and 11.2 mo for VPS ( P = .464). As-treated, per-protocol, and attributable-intervention analyses yielded similar results. CONCLUSION: Postoperative seizure incidence following treatment of PIH was 20% within 2 yr, regardless of treatment modality. Graphical Abstract: